Bedrock characteristics of selected covered karst sites in the Małopolska Upland - Brzozowicz, Dorota (Acta Geographica Lodziensia, 2021)
The article describes the nature of the bedrock in areas in the Małopolska Upland where landforms associated with covered karst processes occur. It seeks to find a relationship between geological structure and the potential for covered karst processes to develop. To this end, it includes a review of the literature on the geological structure of three areas in the mesoregions of Wzgór-za Opoczyńskie, Niecka Włoszczowska and Niecka Solecka. Two of the three sites are located in an area of limestone karst, and the third (located in Niecka Solecka) is an area of gypsum karst. All three sites were filled with sediment in the Holocene, but the forms being studied probably formed much earlier. The author also attempts to reconstruct the relief of the Mesozoic surface as digital terrain models. For this purpose, data was taken from geological drillings contained in geological maps of Poland and developed using GIS software. According to digital terrain models in the form of 3D views all three investigated sites are locat-ed in a depressions in the Mesozoic surface (on the slopes or bottom of the basin). That location and low thickness of impervi-ous deposits has caused that migration of underground water, which can affect karstified rocks with increased intensity.